Implementation of Merit System in the First Placement of Police Academy Graduates and its Implications for Career Development: A Case Study at the National Police Traffic Corps (Korlantas Polri) - Nathania Shinta Belinda Sigit; Basir Basir; Chrysnanda Dwilaksana (Transpublika Publisher, 2025)
This research examines the application of the merit system in the first placement of officers graduating from the Police Academy in the National Police Traffic Corps (Korlantas Polri) and its impact on career development. Using a descriptive qualitative approach, this study analyses the challenges faced by teenage officers placed in administrative positions and their effectiveness on motivation and job satisfaction. Data were collected through in-depth interviews with teenage officers, National Police Traffic Corps (Korlantas Polri) officials, and relevant stakeholders, and supported by documentation studies. The results showed that academic rank-based placements neglect practical abilities and leadership skills. Administrative placements are often perceived to hinder career progression and can lead to demotivation. The research recommends the need for a balance between academic assessment and practical competence in placement, as well as the implementation of more flexible and transparent policies to ensure sustainable career development. The research recommends several measures for HR development in National Police Traffic Corps (Korlantas Polri), including an integrated rotation programme, the use of technology for performance assessment, and cross-field mentoring programmes. In addition, policies that support gender equality and diversity in deployment and strengthening the merit evaluation system are also needed for long-term effectiveness. Periodic evaluation and a holistic approach to human resource management are also needed.